Mediation: international legal standards - Podkovenko, Tetiana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article reveals the role and importance of mediation as an alternative way of solving legal conflicts. It is no accident that mediation as an alternative way of settling disputes is developed in international practice. It is noted that the European Community attaches great importance to mediation as an alternative way of resolving disputes in various spheres of society’s life